Portrait of an Eighth-Century Gentleman : Khālid ibn Ṣafwān in History and Literature - Hämeen-Anttila, Jaakko, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2020)
Portrait of an Eighth-Century Gentleman. Khālid ibn Ṣafwān in History and Literature by Jaakko Hämeen-Anttila is an in-depth study of the eighth-century Umayyad and early Abbasid orator and courtier Khālid ibn Ṣafwān and the development of his character in adab literature. The book collects and translates all his sayings and stories about him culled from a wide range of Arabic and Persian texts. In the book, Hämeen-Anttila studies the mechanisms of change in early narratives, showing how Arabic anecdotes developed and were modified by a series of authors during both their oral and literary transmission, changing a historical person into a literary character. Detailed chapters discuss Khālid in his various roles and analyse the literary techniques of the stories.